Statistical methods for evaluating safety in medical product development - Gould, Lawrence (A. Lawrence) (Chichester, West Sussex, UK : Wiley, 2014)
This book gives professionals in clinical research valuable information on the challenging issues of the design, execution, and management of clinical trials, and how to resolve these issues effectively. It also provides understanding and practical guidance on the application of contemporary statistical methods to contemporary issues in safety evaluation during medical product development. Each chapter provides sufficient detail to the reader to undertake the design and analysis of experiments at various stages of product development, including comprehensive references to the relevant literature. -Provides a guide to statistical methods and application in medical product development -Assists readers in undertaking design and analysis of experiments at various stages of product development -Features case studies throughout the book, as well as, SAS and R code.
Safety graphics / A. Lawrence Gould -- QSAR modeling : prediction of biological activity from chemical structure / Andy Liaw and Vladimir Svetnik -- Ethical and practical issues in phase I trials in healthy volunteers / Stephen Senn -- Phase I trials / A. Lawrence Gould -- Summarizing adverse event risk / A. Lawrence Gould -- Statistical analysis of recurrent adverse events / Liqun Diao, Richard J. Cook, and Ker-Ai Lee -- Cardiovascular toxicity, especially QT/QTc prolongation / Arne Ring and Robert Schall -- Hepatic toxicity / Donald C. Trost -- Neurotoxicity / A. Lawrence Gould -- Safety monitoring / Jay Herson -- Sequential testing for safety evaluation / Jie Chen -- Evaluation of post-marketing safety using spontaneous reporting databases / Ismail Ahmed, Bernard Begaud, and Pascale Tubert-Bitter / Pharmacovigilance using observational/longitudinal databases and web-based information / A. Lawrence Gould.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Drug Evaluation -- methods; Clinical Trials as Topic; Models, Statistical; Pharmacovigilance; Safety Management -- methods; Technology, Pharmaceutical -- standards; Clinical trials -- Statistical methods; MEDICAL -- Pharmacology; Clinical trials -- Statistical methods; Medical; Electronic books